Gain of chromosome 21 increases the propensity for P2RY8::CRLF2 acute lymphoblastic leukemia via increased HMGN1 expression - Page, Elyse C.; Heatley, Susan L.; Rehn, Jacqueline; Thomas, Paul Q.; Yeung, David T.; White, Deborah L. (Frontiers in Oncology, 2023)
Acute Lymphoblastic Leukemia (ALL) patients who harbor gain of chromosome 21, intrachromosomal amplification of chromosome 21 (iAMP21) or have Down Syndrome (DS) have increased expression of genes in the DS critical region (DSCR) of chromosome 21, including the high mobility group nucleosome binding-protein 1, HMGN1. Children with DS are predisposed to developing hematological malignancies, providing insight into the role of chromosome 21 in the development of leukaemias.A 320 KB deletion in the pseudoautosomal region of the X/Y chromosome in leukemic cells resulting in a gene fusion between the purinergic receptor and cytokine receptor-like factor-2 (P2RY8::CRLF2) is a common feature in ~60% of DS-ALL and ~40% of iAMP21 patients, suggesting a link between chromosome 21 and P2RY8::CRLF2. Within an Australian cohort of pediatric B-ALL patients with P2RY8::CRLF2 (n=38), 8 patients harbored +21 and 2 patients had iAMP21, resulting in significantly increased HMGN1 expression. An inducible CRISPR/Cas9 system was used to model P2RY8::CRLF2 and investigate cooperation with HMGN1. This model was then used to validate HMGN1 as an influencing factor for P2RY8::CRLF2 development. Using Cas9 to cleave the DNA at the pseudoautosomal region without directed repair, cells expressing HMGN1 favored repair resulting in P2RY8::CRLF2 generation, compared to cells without HMGN1. CRISPR/Cas9 P2RY8::CRLF2 cells expressing HMGN1 exhibit increased proliferation, thymic stromal lymphopoietin receptor (TSLPR) expression and JAK/STAT signaling; consistent with patient P2RY8::CRLF2 cells. Our patient expression data and unique CRISPR/Cas9 modelling, when taken together, suggest HMGN1 increases the propensity for P2RY8::CRLF2 development. This has important implications for patients with DS, +21 or iAMP21.